Dante and Musculoskeletal Diseases. Issue 18 (15th September 2015) - Manzini, Francesco; Maurina, Matteo; Riva, Michele Augusto
<x xml:space="preserve">Abstract</x> The year 2015 marks the 750th anniversary from the birth of the medieval poet Dante Alighieri. Dante's work seems to provide precious information on medieval knowledge of anatomy and physiopathology of some musculoskeletal structures (including spine). Nonmedical works, including poetry, should be considered as a source for historians of orthopedics.